Atypic Primary Ovarian Lymphoma Presenting with Hypercalcemia: A Rare Case Report - Ezgi ŞAHİN; Faruk KARANDERE; Eda KÜÇÜK; Emine GÜLTÜRK; Şengül Aydın YOLDEMİR; Gülçin YEGEN (Bezmiâlem Science, 2025)
Here, we present a rare case of primary ovarian lymphoma with bilateral ovarian involvement, which manifested with malignant hypercalcemia. A 39-year-old female patient presented to our hospital with lower abdominal pain. Hypercalcemia, anemia, and thrombocytopenia were observed during the examinations. Abdominal ultrasound revealed a mass lesion thought to be associated with an abscess or malignancy in both adnexal areas, as well as mass lesions in bilateral ovaries, along with paraaortic and paraaortocaval lymphadenomegaly on abdominal computed tomography (CT). In the positron emission tomography CT examination, increased fluorodeoxyglucose uptake (SUVmax ranging between 11.5 and 9.5) was observed in the lesions defined on abdominal CT. Bone marrow biopsy performed for thrombocytopenia was found to be compatible with diffuse large B-cell lymphoma (DLBCL). Although this case demonstrates that hypercalcemia can be observed in the course of DLBCL with bilateral ovarian involvement, which is a rare condition, it is also considered significant as it is inconsistent with most of the hypercalcemia mechanisms associated with malignancies described today.